2004
DOI: 10.1111/j.1365-2141.2004.04996.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of TACC3, FGFR3, MMSET and p21 expression with the t(4;14)(p16·3;q32) in multiple myeloma

Abstract: samples showed a joint up-regulation of TACC3, MMSET and p21. Although a poor prognosis is linked with elevated MMSET expression, an extended follow-up period will be required to evaluate the significance of elevated TACC3 and p21 expression in this subgroup of MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 14 publications
5
24
0
Order By: Relevance
“…5). These results were confirmed by immunohistochemical studies of bone marrow biopsy specimens, showing frequent C/T antigen expression among patients with cytogenetic abnormalities and almost universally at relapse (6).…”
Section: Introductionsupporting
confidence: 69%
“…5). These results were confirmed by immunohistochemical studies of bone marrow biopsy specimens, showing frequent C/T antigen expression among patients with cytogenetic abnormalities and almost universally at relapse (6).…”
Section: Introductionsupporting
confidence: 69%
“…In particular, the overexpression of KLF4 is intriguing as it has been reported to mediate the transcriptional repression of the CCND1 promoter (Shie et al, 2000); the low or background levels of CCND1 found in the patients with the t(4;14) (data not shown) may therefore be related to its increased expression. This finding may suggest that cases with the t(4;14) are characterized by the activation of proapoptotic pathways, and thus may be more likely to respond to chemotherapy regimens, consistently with recently reported data (Stewart et al, 2004). During the revision process of this manuscript, a study was published describing the gene expression profiling of t(4;14) MM cases (Dring et al, 2004) whose results only partially overlap with our own, probably because of the different analysis criteria.…”
Section: But Not Pcl Cases) Have Suggested That Normalsupporting
confidence: 41%
“…The dysregulation of TACC3 and MMSET in t(4;14) POS patients has been investigated in several studies. 14,37,38 TACC3 was assayed by qRT-PCR by Stewart et al 37 and a 2-fold increase was reported in t(4;14) POS patients. In our qRT-PCR cohort, we detected an approximate 2-fold difference (REL, 1.17 versus 3.90), however, this difference in mean values was largely due to one outlier and was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%